Risperidone versus haloperidol in children and adolescents with AD: A randomized, controlled, double-blind trial - Miral, Suha; Gencer, Ozlem; Inal-Emiroglu, F. Neslihan; Baykara, Burak; Baykara, Aysen; Dirik, Eray (European child & adolescent psychiatry, 2008)
Objective The aim of the study was to compare safety, efficacy and tolerability of risperidone with haloperidol in the treatment of Autistic Disorder (AD). Method This study was designed as a double-blind, prospective, for a 12-week period. A total of 30 subjects, between the ages of 8 and 18 with AD based on DSM IV criteria, were included in the study. Behavioral Rating Scales were performed by the investigators and the parents. Safety assessment included vital signs, electrocardiogram, electroencephalogram, adverse events, laboratory tests, extrapyramidal symptoms and the side effects. Both treatments were applied in a once daily dosage regimen of 0.01–0.08 mg/kg/day. Results The reduction from baseline in Ritvo–Freeman Real Life Rating Scale (RF-RLRS), sensory motor (subscale I) and language (subscale V) scores were significant in risperidone group ( P < 0.05). Compared to haloperidol, risperidone led to a significantly greater reduction in the Aberrant Behavior Checklist (ABC) and Turgay DSM-IV Pervasive Developmental Disorder (PDD) scale scores ( P < 0.05 and P < 0.01). There was a greater increase of prolactin in the risperidone group, while alanine amino transferase (ALT) had further increased in the haloperidol group. Sensory motor behaviors (subscale I) and language at the end of the 12th week, RF-RLRS sensory motor and language subscale scores decreased in the risperidone group further than the other group ( P < 0.05). Conclusions Risperidone was found to be more effective than haloperidol in the treatment of behavioral symptoms, impulsivity, language skills, and impaired social relations in children with AD. These results demonstrated that both drugs were safe and well tolerated in the treatment of AD.